Effektivitas Peningkatan Keterampilan Menulis Recount Text Melalui Pendekatan Genre Based - Hani, Ummu (Universitas Islam Negeri Sumatera Utara Medan, 2023)
This study intends to ascertain if students at VIII C MTsN 41 Al Azhar Asy Syarif Jakarta in the 2021–2022 Academic Year have improved their recount text writing abilities after using a genre-based method. Classroom action research, which is conducted in two cycles, was the type of research used in this study. The 27 pupils in class VIII C at MTsN 41 Al Azhar Asy Syarif Jakarta who were 27 girls served as the study's subjects. The methods for gathering data used in this study comprised observation sheets and the output of students' writing regarding recount texts, which were part of the teaching process. Using both quantitative and qualitative descriptive methods, the research findings were examined. The results of the data analysis in this study show that there is an improvement in writing ability following the application of the genre-based approach, as can be seen from the students' results of each cycle, where the proportion of students who met the success criteria increased when compared to the pre-test results. Pre-test success requirements were attained by 7 students (21.87%), 21 students (65.63%) for the first cycle, and 25 students (78.13%) for the second cycle. Thus, it can be said that using a genre-based strategy can help students in VIII C MTsN write better recount texts.